STUDI PERBANDINGAN PEMBEBANAN DINAMIS PADA JEMBATAN BETON TERHADAP PEMODELAN FEA - Firdaus, Afridho; Alami, Fikri; Isnaeni, Mohd; Helmi, Masdar (Universitas Lampung, 2023)
The natural frequency of the bridge is the frequency to determine the theoretical and experimental feasibility requirements of the bridge. The natural frequency value is used to determine the theoretical and experimental feasibility requirements of the bridge. Analysis of bridge behavior in resisting dynamic loads and comparing theoretical natural frequencies with field tests on prestressed concrete bridges with a span of 40 m using the line model and the shell model in the sap2000 application. Based on the results of bridge modeling using SAP 2000, the natural frequency on the model line is f○ 3.9876 hz and T 0.2507 seconds, while in shell modeling it is obtained f○ 16.045 hz and T 0.6232 seconds. When given a running load the frequency of the bridge in the shell model is f 15.577 hz and T 0.0642 seconds. The natural frequency value obtained from the model line is 3.9876 hz and the natural frequency from the shell model is 16.045 hz which in the shell model the frequency results are closer to the field test results of 16.67 hz with a ratio of 3.75%. The shell model is used as a comparison to the field model.